OPERATING PARAMETERS OF MTU FOR FERTILIZER APPLICATION - Boyzokov A. K. (Bright Mind Publishing, 2025)
This article examines the rationale for optimal operating parameters and modes of machine-tractor units (MTU) used for mineral fertilizer application. Based on the theory of optimal parameters and mathematical modeling, an analysis of factors influencing unit performance is conducted, including engine power, working width, operating speed, and machine lifting capacity. Particular attention is paid to agronomic requirements for fertilizer distribution quality, shift utilization, and labor cost structure. Using experimental data and regression equations, functional relationships between unit parameters and process quality are established. A multivariate modeling methodology is proposed for determining optimal ratios of operating parameters that ensure increased productivity, reduced present value costs, and economic efficiency of MTA use.
Keywords: MTA, mineral fertilizers, operating parameters, mathematical modeling, productivity, shift utilization rate, economic efficiency, optimization.